Agriculture Supported Communities: Connecting Low-income Communities with Small-scale Vegetable and Fruit Producing Farms (P04-128-19) - Winkels, Renate (Curr Dev Nutr, 2019)
OBJECTIVES: Barriers regarding affordability of and access to fresh vegetables and fruit pose low-income families at increased risk of diet-related diseases. Small farms can play a key role in providing local communities with fresh produce, through farmers’ markets, Community Supported Agriculture (CSA), and other direct marketing strategies. Nevertheless, these farms face specific challenges related to payment terms and conditions and delivery when aiming to connect with low-income communities. Rodale Institute's Agriculture Supported Communities (ASC) program aims to connect small-scale fruit and vegetable farms with low-income communities. This farm-share program sells weekly food boxes with organic fruits and vegetables in cities with major food insecurity problems in Pennsylvania (Allentown and Reading). ASC allows members to pay week-to-week, rather than upfront as in a traditional CSA. ASC shareholders can use federal SNAP dollars to pay for discounted shares or apply for subsidized shares. ASC pick-up sites are located in the targeted communities. Our objective is to evaluate the ASC program and its ability to reach the intended low-income communities. METHODS: In 2016 and 2017, surveys were distributed among ASC shareholders to collect socio-economic data and program satisfaction. In addition, we evaluated how many participants used SNAP to pay for the shares. RESULTS: ASC had 150 shareholders in 2016 and 151 in 2017. In 2016, 89 shareholders (59%) were living in low-income areas in Allentown or Reading, in 2017 this was 76 (50%). In 2016, 43% of the shareholders reported an income < 50k$, in 2017 this was 25%. In 2016, 11 members (7%) paid with SNAP, in 2017 15 members (10%). CONCLUSIONS: ASC reached low-income community members; however, the program also reached a population at the other end of the economic spectrum. This poses challenges for the farmer regarding production and distribution. The farmers within ASC are using these data to optimize production and methods of delivery to meet the needs of low-income communities. In a future project, we hope to evaluate the effect of ASC membership on dietary intake and other health indicators, and measure the social, economic and environmental sustainability of the model. FUNDING SOURCES: For a list of funders see rodaleinstitute.org/asc.